Respectable Citizens: Gender, Family, and Unemployment in Ontario's Great Depression - Korneski, Kurt (Labour / Le Travail, 2011)
The article reviews the book, "Respectable Citizens: Gender, Family, and Unemployment in Ontario's Great Depression," by Lara Campbell.
Keywords: BOOKS -- Reviews; CAMPBELL, Lara; DEPRESSIONS -- 1929; Nonfiction; RESPECTABLE Citizens: Gender, Family & Unemployment in Ontario's Great Depression (Book)